How Follicular Dendritic Cells Shape the B-Cell Antigenome - Kranich, Jan; Krautler, Nike Julia (Frontiers in Immunology, 2016)
Follicular dendritic cells (FDCs) are stromal cells residing in primary follicles and in germinal centers of secondary and tertiary lymphoid organs (SLOs and TLOs). There, they play a crucial role in B-cell activation and affinity maturation of antibodies. FDCs have the unique capacity to bind and retain native antigen in B-cell follicles for long periods of time. Therefore, FDCs shape the B-cell antigenome (the sum of all B-cell antigens) in SLOs and TLOs. In this review we discuss recent findings that explain, how this stromal cell type can arise in almost any tissue during TLO formation and, furthermore focus on the mechanisms of antigen capture and retention involved in the generation of long-lasting antigen depots displayed on FDCs.